DILEMA ETIS PADA CALON AUDITOR: SEBUAH EKSPERIMEN - Ida Rosnidah; Wiwit Apit Sulistyowati; Agung Yulianto (Jurnal Akuntansi Indonesia, 2018)
The ethical dilemma is a condition often encountered by a person when engaged in a relationship that leads to fiduciary responsibility. In fact, this is often faced by the accounting profession when giving his services should be able to avoid conflict of interest. Therefore, this study was conducted on accounting students who have obtained an ethical understanding that acts as a potential auditor. Respondents in this study are accounting students level 3 in accounting majors in the Faculty of Economics Unswagati. This study is conducted through scenarios of cases relating to work or tasks that can lead to actions that conflict with ethical principles of accountants. Where accountants are supposed to apply ethical principles to be dilemma with the existence of such work. Through the scenario of the case, accounting students give their perception whether to perform tasks that are not according to their competence and limited time or the student will refuse the job. The results showed that for accounting students who have gained an understanding of ethics tend to consider many things and find solutions before performing tasks that are less in accordance with the competencies they have. Therefore, it can be concluded that the value of students who have gained a higher ethical understanding.Keywords: ethical dilemma, professional principles, integrity, competence and professional caution